2011
DOI: 10.1177/1947601911405045
|View full text |Cite
|
Sign up to set email alerts
|

The Putative PAX8/PPAR  Fusion Oncoprotein Exhibits Partial Tumor Suppressor Activity through Up-Regulation of Micro-RNA-122 and Dominant-Negative PPAR  Activity

Abstract: IntroductionFollicular thyroid carcinoma (FTC) accounts for up to 20% of all thyroid cancers but is responsible for up to 40% of the deaths associated with this disease.1 In contrast to the wealth of mechanistic information available regarding the pathogenesis of papillary thyroid carcinoma (PTC), the triggering mechanisms of FTC development have remained obscure. PAX8/PPARγ rearrangements, which express the PAX8/PPARγ fusion protein (PPFP), are found in about 36% of FTC.2 Because such rearrangements are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
(68 reference statements)
2
17
0
Order By: Relevance
“…One miRNA ( miR-886-5p ) was removed from the group of 8 confi rmed miRNAs: miR-886-5p , miR-146a-5p , miR-200b-3p , miR-138-5p , miR-187-3p , miR-224-5p , miR-574-3p , and miR-222-3p since it represents a small polymerase III transcript contained in the vault particles of eukaryotic cells [ 23 ] . Despite the partial cross confi rmation according to the fold change criteria the statistical signifi cance of the markers is very low: 3 signifi cant miRNAs in [ 13 ] , 4 in [ 14 ] , and 6 in [ 15 ] out of 27 in total. Furthermore, only miR-885-5p showed a p-value lower than 0.05 in 2 independent data sets [ 13 , 14 ] .…”
Section: Evaluation Of Previously Published Mirnasmentioning
confidence: 96%
See 3 more Smart Citations
“…One miRNA ( miR-886-5p ) was removed from the group of 8 confi rmed miRNAs: miR-886-5p , miR-146a-5p , miR-200b-3p , miR-138-5p , miR-187-3p , miR-224-5p , miR-574-3p , and miR-222-3p since it represents a small polymerase III transcript contained in the vault particles of eukaryotic cells [ 23 ] . Despite the partial cross confi rmation according to the fold change criteria the statistical signifi cance of the markers is very low: 3 signifi cant miRNAs in [ 13 ] , 4 in [ 14 ] , and 6 in [ 15 ] out of 27 in total. Furthermore, only miR-885-5p showed a p-value lower than 0.05 in 2 independent data sets [ 13 , 14 ] .…”
Section: Evaluation Of Previously Published Mirnasmentioning
confidence: 96%
“…Furthermore, only miR-885-5p showed a p-value lower than 0.05 in 2 independent data sets [ 13 , 14 ] . The FDRs for the 27 studied miRNAs were 0.77 ± 0.10 [ 13 ] , 0.77 ± 0.16 [ 14 ] , and 0.66 ± 0.25 [ 15 ] in the respective data sets when given in the mean ± standard deviation form.…”
Section: Evaluation Of Previously Published Mirnasmentioning
confidence: 99%
See 2 more Smart Citations
“…This upregulation was associated with the presence of the PAX8/PPARg fusion protein, which, paradoxically, led to a minimally invasive behavior of tumor. Functional studies revealed that overexpression of miR-122 in a mouse xenograft model resulted in a significant reduction of tumor progression (78).…”
Section: The Potential Of Micrornas In Thyroid Cancer Treatmentmentioning
confidence: 99%